Micrasterias torreyi Bail. var. nurulislamii Aziz var. nov. (Chlorophyceae) from Bangladesh (Bangladesh Journal of Plant Taxonomy, 2010)
Not available.Keywords:  Micrasterias torreyi Bail. var. nurulislamii Aziz var. nov.; Desmid;  Green alga; Bangladesh.DOI: 10.3329/bjpt.v17i1.5399Bangladesh J. Plant Taxon. 17(1): 109-111, 2010 (June)